Rancang Bangun Sistem Informasi Akuntansi Monitoring Perkembangan Proyek Berbasis Web pada PT INTI (Persero) Bandung - Nabila Zahwa Novira Princessa; Perwito .; Rini Surwartika Kusumadiarti; Wahyu Trimastuti (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2022)
PT INTI (Persero) Bandung is a company engaged in telecommunications as the leading supplier for the construction of the national telephone network. Based on the research conducted, the problem is that monitoring project implementation is still done manually. The reports produced are still in the form of hard files, which are not presented quickly and accurately. This study aims to analyze and design a project monitoring information system at PT (Persero) according to the company’s needs so that the company’s operational activities are more effective and efficient. With the project monitoring system, its hoped that it will make it easier to monitor the progress of project implementation and help make decisions for the company. The research method used is qualitative, while the software development method uses a waterfall system. The design is done using UML. Data collection techniques include observation, documentation, interviews and literature study. In making this software using the PHP programming language and XAMPP as localhost. Database storage using MySQL.